Effects of continuous positive airway pressure treatment on arterial stiffness and inflammatory factors in patients with coronary heart disease complicated with obstructive sleep apnea - Liang Wang; Yuanqi Wang; Tiantian Jiao; Linghao Xu; Endong Ji; Sakibur Rahman Tapu; Yehong Liu; Jiming Li (Journal of Cardiothoracic Surgery)
Abstract Background Continuous Positive Airway Pressure (CPAP) treatment brings more benefits than risks to most coronary heart disease (CHD) patients with obstructive sleep apnea (OSA). However, the pathophysiological mechanism by which CPAP treatment improves the prognosis of patients with CHD and OSA remains unclear. The purpose of this study was to clarify whether CPAP can improve arterial stiffness and inflammatory factor levels in CHD patients with OSA, and to further improve prognosis. Method 59 patients with coronary heart disease complicated by moderate to severe sleep apnea were divided into a CPAP treatment group (CPAP + coronary heart disease standard treatment) and a control group (only coronary heart disease standard treatment). Peripheral blood test reports were collected and pulse wave velocity (PWV) measurements were performed for each patient at the beginning, 3 months, and 6 months of treatment. Results After 6 months of treatment, the CPAP group showed more significant improvement in the levels of inflammatory factors such as white blood cell (WBC), neutrophil (N), C-reactive protein (CRP), interleukin-6 (IL-6), procalcitonin (PCT), and PWV than the control group. Conclusion After active treatment with CPAP, arterial stiffness and inflammatory cytokine levels in patients with coronary heart disease and OSA improved. This association should be given more attention in clinical practice, and sleep apnea should be actively treated.